Speciation analysis and health risk assessment of arsenic in seafood from Jiaxing markets - GE Miaohua; ZHOU Ying; ZHANG Xiang; WU Xiaoqiong (Zhongguo shipin weisheng zazhi, 2023)
ObjectiveTo understand the speciation of arsenic in seafood sold in Jiaxing City， the health risks of arsenic exposure due to seafood consumption were evaluated.MethodsTotal arsenic levels and arsenic speciation in 105 samples collected from five seafood categories were detected by high-performance liquid chromatography inductively coupled plasma mass spectrometry. The health risks of inorganic arsenic exposure caused by edible seafood were analyzed based on data for the consumption of aquatic products.ResultsAfter testing 105 samples， the average total arsenic content in the five major types of seafood ranged from 0.85 to 41.85 mg/kg. However， it was primarily in the form of nontoxic arsenobetaine or arsenosugars， with organic arsenic accounting for more than 90% of the total arsenic content. The detection rate of inorganic arsenic was 45.7%， with concentrations ranging from 0.008 to 1.169 mg/kg， and a median value of 0.011 mg/kg. Seafood products with the highest levels of arsenic were mainly seaweed and crustaceans， and one sample exceeded the maximum limit set by the National Food Safety standard GB 2762—2017 for water products by 0.95%. The results of the margin of exposure health risk analysis indicated that the health risks associated with consuming seafood for residents of Jiaxing City were relatively low （margin of exposure values significantly higher than 1）. The risk level was slightly higher for urban residents than for rural residents and slightly higher for females than for males. Increased seafood consumption increased the risk level. Considering factors， such as overall dietary exposure， cooking methods， and transformation during consumption， the risk level would further increase.ConclusionThe health risk caused by inorganic arsenic exposure in seafood is relatively low， but long-term intake of seafood （seaweed and chitin） with high inorganic arsenic content should be avoided.